Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.607906
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying spectral characteristics of fricatives

Abstract: In a search for spectral parameters that can be used to distinguish and to model fricatives, spectral moments, dynamic amplitude, and slope above maximum amplitude were computed for a fricative corpus including sustained fricatives at dierent eort levels, and fricatives in vowel context. Moments varied signicantly by frequency range used in computation. M3 appeared to vary the least across fricative, contrasting with Forrest et al.'s 1988 study. Dynamic amplitude separated sibilants and non-sibilants, as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 6 publications
2
70
0
1
Order By: Relevance
“…The second generalization is expected, since the back of the tongue is not as crucial in forming /s/, and is consistent with the DAC model (Recasens and Espinosa, 2009), which predicts higher variability in the less constrained articulator. The third generalization has been noted indirectly in the literature (Shadle and Mair, 1996;Jongman et al, 2000;Munson, 2001;Jesus and Shadle, 2002), but this work has presented greater detail in the variation of M1 due to context, which will be explored in Sec. IV B.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The second generalization is expected, since the back of the tongue is not as crucial in forming /s/, and is consistent with the DAC model (Recasens and Espinosa, 2009), which predicts higher variability in the less constrained articulator. The third generalization has been noted indirectly in the literature (Shadle and Mair, 1996;Jongman et al, 2000;Munson, 2001;Jesus and Shadle, 2002), but this work has presented greater detail in the variation of M1 due to context, which will be explored in Sec. IV B.…”
Section: Discussionmentioning
confidence: 98%
“…However, several articulatory studies have presented data showing that there is a consistent upward and downward trajectory of the jaw during the production of sibilants (McGowan, 2004;Mooshammer et al, 2007). Acoustic studies of fricative spectra show considerable variability in the time-varying behavior of the spectral moments and other spectral measures through a fricative, even when this temporal variability was not the focus of the study (Shadle and Mair, 1996;Jongman et al, 2000;Munson, 2001;Jesus and Shadle, 2002). For instance, using several example spectra, Munson (2001) showed that the center of gravity of the fricative (first spectral moment) can vary by 500-1000 Hz during an /s/, which may last 100-200 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters that seem to influence identification include gross spectral shapes and peak frequencies ͑Behrens and Blumstein, 1988;Hughes and Halle, 1956;Jongman et al, 2000;Strevens, 1960͒, the first four moments of the spectral energy distribution ͑Forrest et Jongman et al, 2000;Nissen and Fox, 2005;Nittrouer, 1995;Nittrouer et al, 1989;Shadle and Mair, 1996͒, the slopes of lines fitted to spectra in lower and higher frequency regions ͑Evers et Jesus andShadle, 2002͒, formant transition information ͑Jongman et al, 2000;McGowan and Nittrouer, 1988;Nittrouer et al, 1989;Soli, 1981͒, overall amplitude ͑Beh-rens andBlumstein, 1988;Jongman et al, 2000;Stevens, 1971;Strevens, 1960͒, amplitude relative to the neighboring vowel in specific frequency regions ͑Hedrick and Ohde, 1993;Jongman et al, 2000;Stevens, 1985͒, andduration ͑Baum andBlumstein, 1987;Crystal and House, 1988;Jongman, 1989;Jongman et al, 2000͒. Briefly, alveolar fricatives ͑/s/, /z/͒ are characterized by spectral energy ͓above 4 kHz, Hughes and Halle ͑1956͔͒ and major peaks ͓3.5-5 kHz, Behrens and Blumstein ͑1988͒; 6 -8 kHz, Jongman et al ͑2000͔͒ at higher frequencies compared to palato-alveolars ͑/b/, /c/; 2 -4 kHz; ͓Hughes and Halle ͑1956͒, Behrens and Blumstein ͑1988͔͒, which display larger overall relative amplitudes.…”
Section: A Acoustic Properties Of English Fricative Soundsmentioning
confidence: 99%
“…Therefore, the M1 value of /s/ is expected to be higher than that of /$/ because of the shorter front resonating cavity in /s/. This prediction has been confirmed robustly in many acoustic studies of English fricatives (Forrest et al, 1988;Jongman, et al, 2000;Nissen and Fox, 2005;Nittrouer, 1995;Shadle and Mair, 1996;Fox and Nissen, 2005).…”
Section: Introduction a Overviewmentioning
confidence: 59%